Ganglioside GM1 interacts with the serotonin1A receptor via the sphingolipid binding domain - Prasanna, X.; Jafurulla, M.; Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica et Biophysica Acta, 2016)
Glycosphingolipids are minor yet essential components of eukaryotic cell membranes and are involved in a variety of cellular processes. Although glycosphingolipids such as GM1 have been previously reported to influence the function of G protein-coupled receptors (GPCRs), the molecular mechanism remains elusive. In this paper, we have explored the interaction of GM1 with the serotonin1A receptor, an important neurotransmitter receptor that belongs to the GPCR family. To examine the molecular basis of the interaction of GM1 with the serotonin1A receptor, we performed a series of coarse-grain molecular dynamics simulations of the receptor embedded in membrane bilayers containing GM1. Our results show that GM1 interacts with the serotonin1A receptor predominantly at the extracellular loop 1 and specifically at the sphingolipid binding domain (SBD). The SBD motif consists of a characteristic combination of aromatic, basic and turn-inducing residues, and is evolutionarily conserved in case of the serotonin1A receptor. The interaction of the SBD site with GM1 appears to stabilize a 'flip-out' conformation in which W102 of the extracellular loop 1 flips out from the central lumen of the receptor toward the membrane. The population of the 'flip-out' conformation is increased in the presence of cholesterol. Our data strongly suggest that a direct interaction between GM1 and the SBD site of the serotonin1A receptor may occur in vivo. In view of the reported role of GM1 and the serotonin1A receptor in neurodegenerative diseases, GM1-receptor interaction assumes significance in the context of malfunctioning of neuronal GPCRs under such conditions.

Graphical Biology Insights into the dynamic interactions at chemokine-receptor interfaces and mechanistic models of chemokine binding - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (Journal of Structural Biology, 2022)
Chemokine receptors are the central signaling hubs of several processes such as cell migration, chemotaxis and cell positioning. In this graphical review, we provide an overview of the structural and mechanistic principles governing chemokine recognition that are currently emerging. Structural models of chemokine-receptor cocomplexes with endogenous chemokines, viral chemokines and therapeutics have been resolved that highlight multiple interaction sites, termed as CRS1, CRS1.5 etc. The first site of interaction has been shown to be the Nterminal domain of the receptors (CRS1 site). A large structural flexibility of the N-terminal domain has been reported that was supported by both experimental and simulation studies. Upon chemokine binding, the Nterminal domain appears to show constricted dynamics and opens up to interact with the chemokine via a large interface. The subsequent sites such as CRS1.5 and CRS2 sites have been structurally well resolved although differences arise such as the localization of the N-terminus of the ligand to a major or minor pocket of the orthosteric binding site. Several computational studies have highlighted the dynamic protein-protein interface at the CRS1 site that seemingly appears to resolve the differences in NMR and mutagenesis studies. Interestingly, the differential dynamics at the CRS1 site suggests a mixed model of binding with complex signatures of both conformational selection and induced fit models. Integrative experimental and computational approaches could help unravel the structural basis of promiscuity and specificity in chemokine-receptor binding and open up new avenues of therapeutic design.
Keywords: Chemokine receptors; GPCRs; Intrinsically disordered protein domains; protein-protein interactions

Is GCR1 the GPR157 of plants? - Gotkhindikar, Aditi; Chakravorty, David; Sengupta, Durba; Joshi, Manali; Assmann, Sarah M. (PLANT PHYSIOLOGY, 2025)